Research on the Development of Cultural and Creative Products of Handicraft Non-Legacy Tourism Based on Image Processing under the Background of Cultural and Tourism Integration - Anxia Wang, Pingshan Wang, (Design Engineering, 2021)
Folk traditional handicraft is an ornamental and practical art created by working people in their long-term daily production and life, which contains rich cultural heritage through the continuous inheritance of craftsmen of all ages. Based on the background of cultural and tourism integration, this paper makes a detailed analysis of the current situation of the protection and development of intangible cultural heritage, and analyzes the existing problems and shortcomings. This paper explores the non-genetic inheritance and protection methods of traditional handicrafts, integrates non-legacy skills with tourism cultural and creative products, excavates the characteristic culture of tourist attractions, and designs cultural and creative products with both plastic arts and practical functions. The design and production method of image processing can optimize the production of non-legacy handicrafts, so that tourism cultural and creative products not only have the standard of quantitative production, but also contain the temperature of handicraft production. Creating products through tourism will better inherit, innovate and spread intangible cultural heritage.